The Juridical Review the Roles and Responsibilities of Notaries in Credit Agreements in Banking - Prihadi, Rizal Hakim (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
An authentic deed is a deed made in a form determined by law, made by or before a public official in charge for that at the place where the deed was made. Some of the objectives of this study are first to find out the benefits of a credit agreement with a notarial deed when compared to private deed, second to analyze standard agreements in bank credit agreements in relation to the principle of freedom of contract, third to find out the role and responsibilities of notaries in credit agreements on Banking and fourth to find out what factors influence the roles and responsibilities of a notary in the credit agreement at Semarang Banking. The research method used is through statutory and empirical approach methods, using primary data and secondary data.Keywords: Agreement; Credit; Notary.